The Fund's Facilities and Financing Framework for Low-Income Countries. (Policy Papers; Policy Paper ;, 2009)
This paper assesses the adequacy of the Fund's facilities and financing framework for low-income countries (LICs) and proposes reform options. It is part of a broader review of all Fund financial instruments and is timely given the pressure the current global financial crisis is putting on LICs. It builds on previous efforts to adapt the Fund's toolkit to the evolving needs of its LIC members, including creation of the Policy Support Instrument (PSI) and the recent modification of the Exogenous Shocks Facility (ESF). This paper provides the basis for the first stage of the LIC-specific review, with a focus on: (i) gaps and overlaps in the facility architecture for LICs, (ii) design issues such as access, financing terms, and conditionality, and (iii) the concessional resource envelope and funding structure. Based on feedback from Executive Directors and further external consultation, more detailed reform proposals will be prepared in the second stage of the review. The Fund's Facilities and Financing Framework for Low-Income Countries-Supplementary Information March 13, 2009.